Helicobacter pylori prevalence and risk factors among children with celiac disease - Roxana Maxim; Alina Pleşa; Carol Stanciu; Irina Girleanu; Evelina Moraru; Anca Trifan (Turkish Journal of Gastroenterology, 2019)
Background/Aims: The relationship between Helicobacter pylori and celiac disease (CD) remains controversial. The aim of this study was to assess the prevalence and risk factors for H. pylori infection among children diagnosed with CD. Materials and Methods: This study included 70 patients diagnosed with CD at a tertiary referral center in Romania. Age, gender, and indicators of environmental conditions were evaluated via interviews with the children’s caretakers. A multivariable logistic regression analysis was performed to identify the independent predictors for H. pylori infection. Results: Of the 70 patients, 37 (52.9%) were females, and the mean age was 4.04±3.26 years. H. pylori infection was diagnosed in 23 (32.8%) patients, of whom 12 (52.1%) were females, and the mean age was 6.2±4.5 years. Of the total number of children with CD and H. pylori infection, 18 (78.2%) had milder forms of enteropathy (Marsh I-II), whereas the remaining 5 (21.7%) had villous atrophy compared to the other 47 (67.2%) patients who were negative for H. pylori-infection and showed more severe intestinal damage. The development of H. pylori infection was independently related to children with one parent only [odd ratio (OR), 9.04; 95% confidence interval (CI), 1.29-62.89; p<0.001], living in houses without sanitary facilities (OR, 3.88; 95% CI, 1.27-14.22; p=0.016), belonging to low-income families (OR, 8.52; 95% CI, 2.52-71.39; p=0.002), and of parents with a prior history of gastritis (OR, 2.68; 95% CI, 1.49-14.50; p=0.004). Conclusion: Children with CD and H. pylori infection had milder forms of enteropathy compared to children who are negative for H. pylori, suggesting that H. pylori infection may confer some protection against the development of severe degrees of villous atrophy. Cite this article as: Maxim R, Pleşa A, Stanciu C, Gîrleanu I, Moraru E, Trifan A. Helicobacter pylori prevalence and risk factors among children with celiac disease. Turk J Gastroenterol 2019; 30(3): 284-9.